Entrepreneurial Marketing, Innovation, and Halal SME Performance: An Islamic Business Perspective - Athia Zainun Faqiha, Selvy; Murwani, Fulgentius Danardana; Christian, Timotius Febry (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study examines the role of entrepreneurial marketing in enhancing halal-oriented manufacturing SME performance in Indonesia from an Islamic business perspective. In increasingly uncertain and competitive business environments, halal-oriented SMEs are expected not only to achieve financial performance but also to maintain ethical integrity, transparency, and stakeholder trust in accordance with Islamic business principles. Despite the growing importance of halal business practices, limited research has explored how entrepreneurial marketing contributes to SME performance within an Islamic ethical context.Method:  This study employed a quantitative research approach using survey data collected from 75 manufacturing SMEs in Surabaya, East Java, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct effect of entrepreneurial marketing on SME performance, the impact of entrepreneurial marketing on innovation, and the mediating role of innovation in the relationship between entrepreneurial marketing and SME performance.Results: The findings reveal that entrepreneurial marketing has a positive and significant effect on both innovation and SME performance. Furthermore, innovation partially mediates the relationship between entrepreneurial marketing and SME performance, indicating that SMEs with stronger entrepreneurial marketing capabilities are better positioned to enhance innovation and achieve superior organizational outcomes. These findings also suggest that ethical innovation and proactive market orientation contribute significantly to strengthening halal SME competitiveness.Conclusion: Entrepreneurial marketing represents an important strategic capability for improving halal-oriented SME performance while remaining aligned with Islamic business ethics. The integration of entrepreneurial initiatives and innovation enables SMEs to strengthen competitiveness, enhance stakeholder trust, and generate sustainable organizational value. These outcomes are consistent with Islamic principles emphasizing amanah (trustworthiness), adl (fairness), and maslahah(social benefit), highlighting the relevance of ethical business practices in achieving long-term performance.